The effect of water soluble fat replacers and fat reduction on the growth of Lactobacillus sakei and Listeria monocytogenes in broth and pork liver paté. Issue 2 (May 2015) - Samapundo, Simbarashe; Xhaferi, Ramize; Szczcepaniak, Slawomir; Goemare, Olivier; Steen, Liselot; Paelinck, Hubert; Devlieghere, Frank
Abstract The major objective of this study was to evaluate the effect of water soluble fat replacers on the growth of bacteria of importance to processed meats. The first part of the study evaluated the effect of water soluble fat replacers (Beneo™ GR, Beneo™ HPX, STA-LITE WSIII™, Fibersol-2 and Nutriose) on the growth of Lactobacillus sakei and Listeria monocytogenes. Fibersol-2 appears to have the greatest potential for replacing fat without compromising microbiological stability as increase in its water phase concentration resulted in a significant increase in the lag phases of both Lb. sakei and L. monocytogenes. On the other hand, Beneo™ GR stimulated the growth of L. monocytogenes, implying that its use could compromise microbiological safety. In the second part of the study pork liver paté and low fat paté (30% less fat) were challenged with L. monocytogenes. The low fat paté was determined to be microbiologically less stable than the reference paté. This was a result of the low fat paté having significantly higher water activity and pH values than those of the reference paté. The results of this study are of importance to the meat processing industry to make more informed decisions when reducing and/or replacing fat.